Physiological Response of Postharvest Tea Leaves under Vibration Stress - HAO Zhilong, LIN Hongzheng, XU Xingyan, LI Xinlei, YU Xiaomin, YUE Chuan, SUN Yun, JIN Xinyi (Shipin Kexue, 2023)
Shaking is one of the key processes contributing to the quality formation of oolong tea. As an abiotic stress factor, mechanical stress leads to a series of physiological and biochemical changes in plants through various biological effects, which has been widely used in the processing of scented black tea, scented white tea, scented green tea and other tea types to improve their quality. In order to ascertain the physiological changes of green tea leaves in response to mechanical stress, postharvest fresh shoots with 3–4 leaves?from the tea cultivar ‘Tieguanyin’ were evaluated for changes in water content, photosystem II (PS II) parameters, antioxidant enzyme activities and subcellular structure under natural spreading or continuous vibration stress treatment after withering. Compared with naturally spread leaves and withered leaves, the water content in the leaves subjected to vibration stress was not significantly different within the first 30 min of vibration (P > 0.05) but was significantly lower at 60 min (P < 0.05). The green-grassy odor became stronger with increasing vibration time, the refreshing aroma became weaker, and the clear compact lamellar structures of the chloroplast and the thylakoid were gradually loosened, deformed, shrunk, and disrupted. The number of starch granules increased significantly at 5 min, and the number of osmiophilic granules increased significantly at 15 min, resulting in the formation of aggregates. The actual photosynthetic efficiency Y (II) and photochemical quenching coefficient (qP) of PS II generally showed a decreasing trend with increasing vibration time, and the electron transfer rate (ETR) declined initially and then rose. The Y (II) and ETR at 5 and 10 min of vibration were significantly lower than those observed in naturally spread leaves (P < 0.05). The quantum yield Y (NO) of non-regulated energy dissipation increased with the prolongation of vibration stress treatment time, and was significantly higher than that of naturally spread leaves at 30 min (P < 0.05). The relative conductivity of tea leaves under vibration stress for 10 min was significantly higher than that of naturally spread leaves (P < 0.05). The activities of ascorbate peroxidase, dehydroascorbate reductase and glutathione reductase in tea leaves under vibration stress for 5 and 10 min were higher than those in naturally spread leaves. Vibration treatment (for up to 30 min) did not show significant variations in water content, but enhanced the green-grassy odor. Continuous vibration treatment caused cell injuries by increasing the cell membrane permeability, thereby facilitating the release of intracellular contents and increasing cell conductivity. At the subcellular level, vibration treatment promoted thylakoid degradation and severely damaged chloroplasts, thus destroying PS II stability. Meanwhile, it protected tea leaf cells against mechanical stress-induced damage by elevating the activities of defense enzymes. Taken together, this study lays a foundation for the regulating of shaking during the processing of oolong tea.